Content Validity: Air Pressure and Bounce Measurement Tool for Soft Tennis Balls - Yoga Irawan; Ranu Baskora Aji Putra; Rivan Saghita Pratama; Hermawan Pamot Raharjo (Journal of Physical Education and Sports, 2026)
This study was conducted to address the lack of objective and accurate measurement tools for assessing air pressure and ball bounce in soft tennis, which are crucial factors affecting game quality and fairness. Currently, ball inspection is often performed using subjective and manual methods, leading to inconsistent decisions by referees. The objective of this research was to develop and examine the content validity of an air pressure and ball bounce measuring instrument specifically designed for soft tennis balls. The study employed a research and development (R&D) approach using mixed methods. Content validity was evaluated through expert judgment involving three experts: a national soft tennis referee, a sports technologist, and an electronics expert. Data were collected using a questionnaire consisting of 20 items rated on a five-point scale and analyzed using Aiken’s V formula. The results showed that all items achieved Aiken’s V values ranging from 0.83 to 1.00, indicating good to excellent content validity. The findings demonstrate that the developed instrument is valid, relevant, and suitable for measuring soft tennis ball quality. Importantly, the instrument has the potential to improve measurement accuracy, reduce referee subjectivity, and support standardized ball inspection procedures in soft tennis competitions